Knowledge, Attitude, Practice of Pregnant Women and Husband’s Support on the Implementation of Pregnancy Exercise - Maringka, Netania Xaviera; Hamzah, Adilla Nur; Marcellin, Chintya; Satria, Ongky; Laurentina Nainggolan, Julita Dortua (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objectives: This study aims to evaluate the knowledge and attitudes of pregnant women and assess the level of support from their partners regarding the adoption of pregnancy exercises in the Tangerang region. Methods: A quantitative analysis was employed for this study, utilizing a cross-sectional study design. Results: Data were collected from 49 respondents, revealing a statistically significant relationship (p=0.031) between the knowledge of pregnant women and the implementation of pregnancy exercises. Additionally, a highly significant association (p<0.001) was observed between the attitudes of pregnant women and their adoption of pregnancy exercises. However, no significant relationship was found between the level of support from husbands and the implementation of pregnancy exercises. Conclusion: This study concludes that there is a significant correlation between the knowledge and attitudes of pregnant women and the adoption of pregnancy exercises. Keywords: attitude, husband support, knowledge, pregnancy, pregnancy exercise, prenatal yoga